Avaliação do produto do cuidar em enfermagem em hospitais especializados - Chotolli, Mayara Ruiz (2017)
Objectives: To access the Nursing care product in hospitalization units of specialized hospitals, identifying the items that most have contributed to the total amount of scores; to compare the obtained product between hospitals, hospitalization units and work shifts and verify an association between demographic and professional variables of the evaluators and the care product. Method: This study is characterized as a cross-sectional descriptive of quantitative nature in the modality of evaluation study. The investigation was from June 2015 to April 2016 in specialized units of two hospitals in the Northwest region of São Paulo state - Barretos Cancer Hospital (HA) and the Hospital of Child and Maternity Hospital of São José do Rio Preto - HCM (HB). To obtain the information, a validated instrument for evaluating the care product (APROCENF) and two forms were used - one for the evaluators´ personal and professional characterization and another for data recording. Results: A total of 138 evaluations of the care product were performed, being 73 in the HA and 65 in the HB by 44 clinical nurses (HA n = 31 HB n = 13) during the work shifts. The scores ranged from 14 (HA) to 29 (HB), with a mean value nearly 24, with a predominance of the good category in both hospitals. When analyzing the gradations of the instrument in hospitals, a statistical difference (p <0.01) was found by the Mann-Whitney test. A correlation of -0.37 between the mean score and age was observed in the HA, and -0.23 when related to the time in the institution. No statistical difference between work shifts was observed when hospitals were independently compared. There was significance (p = 0.01) only when they were jointly analyzed and this significance was for the night shift (p = 0.03). The items that most contributed to the total score were: Attention patient / family, Care / needs, Care planning, and Resources needed to provide assistance. Interaction and multidisciplinary action could be stood out as the item with minor contribution. Conclusion: The product of care was considered predominantly "good" in both hospitals. The association between the total score and the demographic and professional variables was weak. The instrument allowed to identify critical aspects of Nursing work in different units and / or specialized services, providing guidelines to nurses for strategic planning, decision-making and change management.